Effect of children’s game addiction levels on sleep and academic achievement in the covid-19 process - Dağ, Yeliz Suna; Yayan, Yakup Ömür (Journal of Dependence, 2021)
Objective: The aim of this study is to examine the effects of children’s game addiction levels on their sleep and academic success. Method: The study was conducted with 123 parents and children. In the study,‘Digital Game Addiction Scale for Children’ and ‘Children’s Sleep Habits Questionnaire’. Results: 52% of the children included in the study were girls, the average age was 10.21 ± 1.30 and their academic achievement was mostly good. 92% of the children were in the risk group for digital game addiction and all of them had sleep problems. The availability of a computer/tablet at home, the time children spend on the computer/tablet and being allowed to spend time on the computer/tablet affect children’s sleep.There was a positive correlation between the children’s academic achievement and their sleep time while there was a negative correlation between children’s academic achievement and the total score and subscales of game addiction. In addition, the digital game addiction scale and its subscales positively affected the total scores of sleep anxiety, night awakenings, parasomnia, daytime sleepiness and sleep scale. Conclusion: Children were in the risk group for digital game addiction and had sleep problems. In this direction, it is recommended to provide education and counseling according to the technology use and sleep needs of children.